What matters? Keynote address July 6th, 2015: 8th International Drama in Education Research Institute, National Institute of Education, Nanyang Technological University, Singapore. Issue 1 (2nd January 2018) - Saxton, Juliana
ABSTRACT: As we prepare for the 9th IDIERI in New Zealand, this paper revisits the issues foregrounded at the 2015 Institute and offers possible prompts for considering the state of our art today. A meditation on the concept of 'open culture' – the Institute theme – this keynote explores Kuo Pao Kun's injunction 'to extend one's self beyond one's own culture' and how and why our capacity for that 'extension' is so constrained. Exploring the 'famine of quality conversation' and exampled by a case study, the author offers three possibilities that may make it difficult for 'the light to get in' and ways in which our own practice may act as a deterrent to that occlusion.